Cognitive domain analysis (LOTS and HOTS) assessment instruments made by primary school teachers - Puji Hartini; Hari Setiadi; Ernawati Ernawati (Jurnal Penelitian dan Evaluasi Pendidikan, 2021)
This research aims to qualitatively analyze the validity of items and the suitability of cognitive domains (LOTS and HOTS) assessment instruments on natural science subjects made by elementary school teachers in East Jakarta. The method used is descriptive qualitative method with analysis of observations, documents in the form of teacher-made assessment instruments, interviews, and results of expert validation which are analyzed by comparison analysis techniques. The observation results show that all schools use the questions that are available in textbooks owned by students for assessment and the results of analysis of teacher-made assessment instruments validated by experts, there are 81.25% items included in the LOTS category, while 18.75% are included in the HOTS category, so it can be concluded that: (1) the instruments used by elementary school teachers in East Jakarta have fulfilled the content validity, (2) the cognitive domain (LOTS HOTS) on the instruments used by elementary school teachers are proportional, (3) the quality of assessments conducted by elementary school teachers in East Jakarta is good with a record of improvement, (4) the implementation of assessments conducted by elementary school teachers in East Jakarta has followed the assessment standards provided by the government.